HOW IS E-LEARNING USEFUL TO TEACHERS & STUDENT TEACHERS: USING BE-SMART FOR READING AND LISTENING CLASS - Tri Wahyuni Floriasti (MAJALAH ILMIAH PEMBELAJARAN, 2012)
The powerful information resources of the Internet hold tremendous promise for students and teachers. Teachers can find lots of useful resources on the Internet, which they can use in their instructions.  E-learning than can be found on the internet is a hi-tech way, which is widely used in teaching learning process. Yogyakarta State University provides students with e-learning, which is known as Be-smart, in order to meet the upper standard of transferring knowledge and facilitating students to open the global world. It can be the train for UNY to get what people of say World Class University. Thus, this article will describe the use of Be-smart in teaching listening and reading in English Education Department of Faculty Languages and Arts.